From Curriculum to Textbooks — Post 2005 Revised Textbooks and Social Exclusion - SHARMA, GUNJAN (THE PRIMARY TEACHER, 2015)
This paper examines how a curricular policy is translated into practice. To do so it reviews some selected school textbooks that have been revised based on National Curriculum Framework–2005 (NCF–2005). It focusses on mapping how social exclusion has been addressed in these textbooks. These findings are supported with fieldwork in a government primary school, and discussions with school teachers and Sarva Shiksha Abhiyan functionaries.